Glucitol-core containing gallotannins-enriched red maple (Acer rubrum) leaves extract alleviated obesity via modulating short-chain fatty acid production in high-fat diet-fed mice. (July 2020) - Li, Liya; Ma, Hang; Liu, Tingting; Ding, Zhanjun; Liu, Wei; Gu, Qiong; Mu, Yu; Xu, Jun; Seeram, Navindra P.; Huang, Xueshi; Xu, Jialin
Graphical abstract: Highlights: MLE alleviated diet-induced obesity without impacting energy intake. MLE ameliorated liver steatosis and local low-grade inflammation in HFD-fed mice. MLE increased colon-derived total SCFAs and n -butyric acid production. The anti-obesity effects of MLE are partially due to the modulation of gut flora. Abstract: Glucitol-core containing gallotannins (GCGs) are characteristic constituents of the red maple ( Acer rubrum ) species. To pursue the development of red maple for nutraceutical applications, GCGs-enriched red maple leaves extract (MLE) was evaluated for its effects on obesity, gut dysbiosis and short chain fatty acids (SCFAs) production. Our results demonstrated that MLE alleviated high-fat diet-induced obesity, reduced body weight gain and fat mass, improved liver steatosis and insulin resistance, and mitigated adipose hypertrophy and inflammation. Additionally, MLE increased total SCFAs, acetic acid and n -butyric acid content, but exerted no impact on propionic acid production. Moreover, MLE modulated gut microbiota community structure and certain bacteria relative abundance, including Prevotella and Eubacterium . Our work firstly reports a potential association between colon-derived SCFAs production and metabolic improvement due to GCGs-enriched red maple leaves extract administration, and highlights the utilization of red maple gallotannins as a dietary ingredient for preventing obesity and related metabolic diseases.